2023
DOI: 10.1073/pnas.2120536120
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic outcomes and errors in fibrous environments

Abstract: During mitosis, cells round up and utilize the interphase adhesion sites within the fibrous extracellular matrix (ECM) as guidance cues to orient the mitotic spindles. Here, using suspended ECM-mimicking nanofiber networks, we explore mitotic outcomes and error distribution for various interphase cell shapes. Elongated cells attached to single fibers through two focal adhesion clusters (FACs) at their extremities result in perfect spherical mitotic cell bodies that undergo significant 3-dimensional (3D) displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…1e ). The observation that increased inter-kinetochore separation distance corresponds to faster mitotic durations matches our previous observations 9 . Cytokinesis events captured from live cell imaging revealed substantial reorientation of the division axis in cells under ECM-confinement ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…1e ). The observation that increased inter-kinetochore separation distance corresponds to faster mitotic durations matches our previous observations 9 . Cytokinesis events captured from live cell imaging revealed substantial reorientation of the division axis in cells under ECM-confinement ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 91%
“…In our previous work, we showed that cells attached to two fibers (12 µm apart) underwent division by balling up while being held by RFs originating from four adhesion sites on fibers (Fig. 1a(i), Supplementary Movie S1) 9 . Often the cells got trapped between the two fibers, causing them to bow outwards (Fig.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Previously, we showed that cellular shapes can be tuned to the underlying fiber network, with actin stress fibers aligning along ECM-fibers in cells attached to single and multiple parallel fibers, and intersecting actin networks in cells attached to a crosshatch network of fibers [49, 50]. In a subsequent study, the underlying actin networks were found to regulate mitotic outcomes through actin retraction fibers connecting the rounded mitotic cell body to interphase adhesion sites [51]. In both studies, while the patterning of actin networks matched the arrangement of underlying ECM networks, it was unclear how far the effect of adhesions on fibers was extended to shape the actin networks.…”
Section: Resultsmentioning
confidence: 99%
“…Fibers were spun on hollow 5 × 5 mm metal scaffolds. The first layer of fibers deposited were large diameter fibers ∼ 2 µ m ( M w = 15 × 10 6 g/mol) followed by an orthogonal layer of 200 nm ( M w = 2.5 × 10 6 g/mol) fibers with spacing varying from 7 to 20 µ m to achieve a variety of cell shapes (elongated on single fibers and parallel-shaped cells on two or more fibers) [51, 69, 70]. Additionally, crosshatch networks of 200 nm fiber diameters were also prepared with spacing varying from 7 to 20 µ m [50, 71] to achieve polygonal and kite-shaped cells on multiple fibers.…”
Section: Methodsmentioning
confidence: 99%